Suppression of lps-stimulated BV2 microglial cells and attenuation of memory deficit in mice by lactobacilli-fermented milk / Nurul Huda Musa - Musa, Nurul Huda (2013)
Neuroinflammation has been implicated as a common cause of neurodegenerative disease including Alzheimer’s disease (AD). It results primarily from the activation of microglia that produces neurotoxic mediators and pro-inflammatory cytokines leading to neuronal death. Currently, research support nutritional interventions that include foods enriched with antioxidants to prevent AD and there is an increasing interest in the use of probiotics as a neuroprotective agent. In the present study, the protective effect of six lactobacilli strains (LAB 1, LAB 9, LAB 10, LAB 11, LAB 12 and LABPC) fermented in three different milk types [soymilk (SM-LAB), cow’s milk (CM-LAB) and goat’s milk (GM-LAB)] against lipopolysaccharide (LPS)-induced neuroinflammation in microglial BV2 cells was determined in vitro. The ability of the lactobacilli-fermented milk types to prevent memory deficit in LPS-induced mice was also investigated. Anti-inflammatory response against nitric oxide (NO) and CD40 expression was measured in BV2 cells. Mice were orally administered with SMLAB, CM-LAB or GM-LAB for 28 days and learning and memory behavior were assessed using Morris water maze test. Brain tissues were used to measure acetylcholinesterase (AChE) activity, antioxidative activity, lipid peroxidation activity [malondialdenyde (MDA)], nitrosative stress parameters (NO), meanwhile, serum was collected for cytokine analysis (MCP-1, IL-ip and IL-6 ). In general, all the lactobacilli strains fermented in soymilk (SM-LAB 1, 9, 10, 11, 12 and SM-LABPC) and goat’s milk (GM-LAB 1, 9, 10, 11, 12 and SM-LABPC) significantly (p<0.05) inhibited NO production without affecting cell viability. In cow’s milk, only CMLAB 9 and CM-LABPC decreased the NO level. However, the CD40 expression level was not significantly affected. Administration of CM-LAB, GM-LAB and SM-LAB (LAB 9 and LABPC) attenuated LPS-induced memory deficit as shown by the Morris water maze test. Furthermore, lactobacilli fermented in all milk types enhanced the level of antioxidant enzymes; SOD, GSH, and GPx and substantially reduced MDA level in LPS-induced mice. For AChE activity, only CM-LAB and GM-LAB significantly (c><0.05) reduced AChE level, while only SM-LAB significantly (p<0.05) increased catalase activity. The cytokines were reduced in SM-LAB, but for CM-LAB and GM-LAB, the effects of unfermented milk (UCM and UGM) were even greater. In conclusion, results from the present study suggest the ameliorating effect of lactobacilli-fermented milk on LPS-induced neuroinflamation and memory deficit to be mediated via anti-inflammatory, inhibition of AChE and antioxidative activities. Dietary interventions with probiotics fermented milk have the potential to prevent neuroinflammation and improve memory in AD.